Cardioimmunology: the immune system in cardiac homeostasis and disease. Issue 12 (December 2018) - Swirski, Filip; Nahrendorf, Matthias
Abstract The past few decades have generated growing recognition that the immune system makes an important contribution to cardiac development, composition and function. Immune cells infiltrate the heart at gestation and remain in the myocardium, where they participate in essential housekeeping functions throughout life. After myocardial infarction or in response to infection, large numbers of immune cells are recruited to the heart to remove dying tissue, scavenge pathogens and promote healing. Under some circumstances, immune cells can cause irreversible damage, contributing to heart failure. This Review focuses on the role of the immune system in the heart under both homeostatic and perturbed conditions. Recent studies have characterized complex interactions between resident and infiltrating immune cells in the heart and cardiac cells, including cardiomyocytes, fibroblasts and endothelial cells. This Review explores the role of immune cells in cardiac development and physiological function, as well as heart disease.